PACKET SCHEDULING ALGORITHM VIA THE SINK NODES FOR THE ENERGY EFFICIENT MULTITARGET TRACKING IN WSNS - Manikrao, Bukey Chetan; Biradar, Vijayalaxmi; Shinde, Sagar B. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Multitarget tracking is important research problem in WSNs since last decade. Recently improved solutions have been proposed for the same. However, some research problems that yet to address. Targets with varied importance levels invade the monitoring area, making threat assessment challenging. Some critical monitoring locations may miss high-level targets. Tracking delay reduction, energy consumption reduction, and overall network performances enhancement still needs to be enhanced.